Knowing Yourself to educate. Performative autoethnography as a self-reflexive method for research and education - Koeltzsch, Grit Kirstin (2021)
Autoethnography has gained importance as a methodological approach within empirical research, however, self-interrogation and critical self-exploration also plays a key role in our educational practice. In this paper, the performance titled: “Pachamama: Corporealities of an Andean-peasant woman” (Koeltzsch, 2020) is discussed involving creative processes to reveal research results, and emphasizing the body as an interface between the social environment, society and scholarly work. In this case, experimentation beyond textuality is achieved through systematic introspection, which led to a visual-performative result used for a higher-education class of American History in Argentina. I argue that autoethnography makes it possible to locate the researcher’s history and culture in relation to others, but it also reflects critically on other analytical categories, such as work and gender, in this case. I conclude that this approach can help to draw new lines for a dialectical self/others comprehension, without dividing roles into observer, participant, or analyzer, but also to understand the bodily performance of ourselves and others as an act of intervention, resistance, a form of criticizing, and a way of revealing agency regarding contents and performers in a subaltern situation.